Optimizing Various Operational Conditions of Hydrazine Single Cell for a Short Stack System - Jihyeon Park; Jaeyoung Lee (Advanced Energy & Sustainability Research, 2023)
Although hydrazine fuel cells (HzFCs) have various advantages such as a high theoretical potential, low operating temperature, and no carbon dioxide emission, only a couple of studies on HzFC stack have been reported due to the peculiarity of using an anion exchange membrane and the toxic issue of highly concentrated hydrazine fuel. Herein, how the power output performance in a single‐cell system is affected by various operational factors of cell temperature, humidification level, pressurization, fuel concentration, and stoichiometric value is investigated and then a home‐made short stack consisting of five single cells (HzFC‐5S) to evaluate the difference between the single cell and the stack is built up. Confirmation that the optimization point in the single‐cell does not apply to the short stack can be meaningful in accessing its possible commercialization process for portable and mobile devices.